The basic keratin 10-binding domain of the virulence-associated pneumococcal serine-rich protein PsrP adopts a novel MSCRAMM fold. Issue 1 (January 2014) - Schulte, Tim; Löfling, Jonas; Mikaelsson, Cecilia; Kikhney, Alexey; Hentrich, Karina; Diamante, Aurora; Ebel, Christine; Normark, Staffan; Svergun, Dmitri; Henriques-Normark, Birgitta; Achour, Adnane
Abstract : Streptococcus pneumoniae is a major human pathogen, and a leading cause of disease and death worldwide. Pneumococcal invasive disease is triggered by initial asymptomatic colonization of the human upper respiratory tract. The pneumococcal serine-rich repeat protein (PsrP) is a lung-specific virulence factor whose functional binding region (BR) binds to keratin-10 (KRT10) and promotes pneumococcal biofilm formation through self-oligomerization. We present the crystal structure of the KRT10-binding domain of PsrP (BR187–385 ) determined to 2.0 Å resolution. BR187–385 adopts a novel variant of the DEv-IgG fold, typical for microbial surface components recognizing adhesive matrix molecules adhesins, despite very low sequence identity. An extended β-sheet on one side of the compressed, two-sided barrel presents a basic groove that possibly binds to the acidic helical rod domain of KRT10. Our study also demonstrates the importance of the other side of the barrel, formed by extensive well-ordered loops and stabilized by short β-strands, for interaction with KRT10.